2019
DOI: 10.4081/aiua.2019.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The role of anticholinergic therapy based on the upoint system in the treatment of chronic prostatitis

Abstract: Objective: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common problem and severely impairs the quality of life (QoL). We aimed to investigate the effects of different treatment options on voiding symptoms and QoL in patients with urinary phenotype according to the UPOINT system. Matherial and methods: Ninety-six patients with NIH category II,III CP/CPPS were included in the study prospectively. After the diagnosis, the questionnaires including NIH Chronic prostatitis Symptom Index (NIH-CPSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…While there is sufficient evidence of the efficacy of anticholinergic drugs in treating LUTS in general, there is mixed data about their effectiveness in UCPPS patients. While some studies reported little to no improvement in symptom severity or QoL measures in CP/CPPS patients (Kim et al, 2011), others determined that anticholinergic drugs significantly decreased CP/CPPS symptoms in patients with the urinary-centric phenotype when combined with alphablockers or antimuscarinic drugs (Narter et al, 2019). Additional clinical trials on women with IC/BPS have demonstrated that intravesical instillations of anticholinergic drugs can reduce LUTS and pain in combination with other therapies (Barbalias et al, 2000;Raisin et al, 2023).…”
Section: Additional Therapeutic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is sufficient evidence of the efficacy of anticholinergic drugs in treating LUTS in general, there is mixed data about their effectiveness in UCPPS patients. While some studies reported little to no improvement in symptom severity or QoL measures in CP/CPPS patients (Kim et al, 2011), others determined that anticholinergic drugs significantly decreased CP/CPPS symptoms in patients with the urinary-centric phenotype when combined with alphablockers or antimuscarinic drugs (Narter et al, 2019). Additional clinical trials on women with IC/BPS have demonstrated that intravesical instillations of anticholinergic drugs can reduce LUTS and pain in combination with other therapies (Barbalias et al, 2000;Raisin et al, 2023).…”
Section: Additional Therapeutic Considerationsmentioning
confidence: 99%
“…Block the action of acetylcholine Barbalias et al, 2000;Gerretsen & Pollock, 2011;Ghossein et al, 2023;Kim et al, 2011;Narter et al, 2019;Raisin et al, 2023…”
Section: Syndromeunclassified